Diagnostic Accuracy of Next Generation Sequencing Panel using Circulating Tumor DNA in Patients with Advanced Non-Small Cell Lung Cancer: A Systematic Review and Meta-Analysis - Mariana M. Sebastião; Rodrigo S. Ho; João Paulo V. de Carvalho; Micha Nussbaum (Journal of Health Economics and Outcomes Research)
**Background/Objectives:** Until now, no meta-analysis has been published to evaluate the diagnostic performance of next-generation sequencing (NGS) panel using circulating tumor (ctDNA) in patients with advanced non-small cell lung cancer (aNSCLC). The aim of the study was to carry out a systematic review and a meta-analysis in order to determine the accuracy of NGS of ctDNA to detect six oncogenic driver alterations: epidermal growth factor receptor (EGFR); anaplastic lymphoma kinase (ALK); ROS proto-oncogene 1, receptor tyrosine kinase (ROS-1); serine/threonine-protein kinase B-RAF (BRAF); RET proto-oncogene (RET); and MET proto-oncogene, receptor tyrosine kinase (MET) exon 14 in patients with aNSCLC. # Methods MEDLINE/PubMed, Cochrane Library, Latin American and Caribbean Health Sciences Literature (LILACS), and Centre for Reviews and Dissemination databases and articles obtained from other sources were searched for relevant studies that evaluate the accuracy (sensitivity and specificity) of NGS using ctDNA in patients with aNSCLC. The studies were eligible when NGS of ctDNA was compared with tissue tests to detect at least one of the six oncogenic driver alterations. Diagnostic measures (sensitivity and specificity) were pooled with a bivariate diagnostic random effect. All statistical analyses were performed with software R, v.4.0.0.